The shadow archetype as stimulation for descriptive writing : a postcolonial gothic pedagogy - Ahmad Muhyiddin Yusof; Ruzy Suliza Hashim; Anita Harris Satkunananthan (Penerbit Universiti Kebangsaan Malaysia, 2021)
Students at the UiTM Seri Iskandar Campus were found to have a limited ability to describe and expand creatively on subjects in class, particularly during their in-class evaluations. A first evaluation determined that this was due to a lack of writing stimulus in class. Therefore, we initiated the incorporation of two figures from horror fiction and folklore (Cthulhu and the Pontianak) into a type of creative stimulation aimed at improving pupils' descriptive writing abilities. This was accomplished by applying the Jungian shadow archetype in action-based research, incorporating the psychological stimulus into class-based activity. This had the effect of providing and thus empowering the students to improve their descriptive writing. Additionally, students benefitted from this recommended archetype-related stimulation by expanding their creativity and vocabulary via the process of defining the subject. The primary intention behind the research methodology of incorporating these two figures in class-based activity is to discern the points of divergence in which gender-based horror figures provide more psychological impact. The research objective is to investigate the ways in which the shadow archetype as a stimulus enables students to express themselves better, first through speech and then through descriptive writing. It is shown that students responded well to this Gothic pedagogical method and were able to express themselves better. The findings indicate that students exhibited increased performance in their descriptive ability and displayed understanding of the concept of the shadow archetypes. The study's conclusion is that utilising psychological cues promotes improved writing in Malaysian students.